2020
DOI: 10.1016/j.ijcard.2019.07.086
|View full text |Cite
|
Sign up to set email alerts
|

Atrial fibrillation as a clinical characteristic of arrhythmogenic right ventricular cardiomyopathy: Experience from the Nordic ARVC Registry

Abstract: Background: Recent studies in arrhythmogenic right ventricular cardiomyopathy (ARVC) patients have drawn attention to atrial fibrillation (AF) as an arrhythmic manifestation of ARVC and as an indicator of atrial involvement in the disease progression. We aimed to assess the prevalence of AF in the Scandinavian cohort of ARVC patients and to evaluate its association with disease clinical manifestations. Methods: Study sample comprised of 293 definite ARVC patients by 2010 Task Force criteria (TFC2010) and 141 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Но только у 2 (2,5% обследованной когорты) пробандов с вероятным диагнозом АКПЖ в результате ДНК-диагностики нами были выявлены варианты IV-V класса патогенности, и удалось поднять статус диагноза до достоверного. Данные нашего исследования показывают, что наибольшая выявляемость мутаций наблюдается у пробандов, имеющих развёрнутую клиническую [24]. В нашей группе больных мутации были обнаружены в генах PKP2, DSG2 и DSP.…”
Section: Discussionunclassified
“…Но только у 2 (2,5% обследованной когорты) пробандов с вероятным диагнозом АКПЖ в результате ДНК-диагностики нами были выявлены варианты IV-V класса патогенности, и удалось поднять статус диагноза до достоверного. Данные нашего исследования показывают, что наибольшая выявляемость мутаций наблюдается у пробандов, имеющих развёрнутую клиническую [24]. В нашей группе больных мутации были обнаружены в генах PKP2, DSG2 и DSP.…”
Section: Discussionunclassified
“…Up to 15-20% of ARVC patients enrolled in large and well-characterized cohorts were reported to suffer from episodes of atrial arrhythmias, with AF being the most common one [3,7,8]. Atrial arrhythmias in these patients may develop as part of a primary pathogenic process (atrial cardiomyopathy) due to desmosomal/connexome impairment in the atria or as a consequence of atrial dilation following depressed ventricular function and dilation.…”
Section: Atrial Arrhythmias and Arvcmentioning
confidence: 99%
“…The atria of patients with ARVC have been shown to be dilated and their function impaired, with the right atrium (RA) being predominantly affected by this process [3][4][5]. Considering electrocardiographic features, Platonov PG et al first described an altered electrical conduction within the atria of patients with ARVC [6], and subsequent cohort studies reported a high rate of atrial arrhythmias in ARVC [3,7,8]. Particularly, atrial fibrillation (AF) and atrial flutter (AFl) were shown to be more frequent and presented at a younger age in patients with ARVC as compared to the general population [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…AF is an arrhythmic manifestation of ARVC and an indicator of atrial involvement in disease progression. The prevalence correlates with ARVC diagnostic score -considerably increasing with a diagnostic score of 4 and increases further with increased diagnostic score [61].…”
Section: Atrial Fibrillationmentioning
confidence: 95%
“…The involvement of the LV leading to systolic dysfunction may also be associated with complications such as AF and thromboembolic events [62]. The development of atrial myocardial substrate in ARVC may be influenced by genetically determined desmosomal dysfunction [61]. AF may also result from the same mechanisms responsible for fibrotic replacement of the myocardium in the RV walls and occurs in parallel with the involvement of the ventricular myocardium [61,62].…”
Section: Atrial Fibrillationmentioning
confidence: 99%